HEALTH EXPENDITURE ANALYSIS IN PATIENTS WITH PREGNANCY-LABOR COMPLICATIONS IN SURABAYA - Ernawaty Ernawaty; Dewi Sri (Indonesian Journal of Health Administration, 2022)
Background: Healthcare spending has serious social and economic consequences for familie, such as financial constraints and psychological distress. Expenditure caused by obstetrics complications has an impact on total household spending. One person’s health expenditure can influence their family members’ welfare. Aims: This study analyzed health expenditure of patients experiencing preeclampsia, eclampsia, and postpartum hemorrhages. Methods: This study utilized a descriptive observational research design with a cross-sectional approach. The research sample consisted of 135 women who gave birth in November to December 2018. Multistage random sampling was used since the respondents were selected from regions of Surabaya. Results: Respondents of pregnancy and delivery complication with catastrophic health expenditure was eclampsia suffered by 40 respondents, 71 respondents with medium income financing Rp3,800,000.00, 64 respondents with medium household expenditure (monthly income of Rp2,001,000.00 - Rp3,000,000.00). As many as 62 respondents had social security agency for health without contribution beneficiaries, 62 respondents had one employed family member, and 66 respondents had 5-7 family members. Conclusions: The majority of respondents in Surabaya in 2019 experienced a 10% increase of total household expenditure while undergoing treatment. The government continues to increase subsidies for health service facilities that mostly serve the indigen population.